Improving Esthetic and Functional Outcomes of Severe Habsburg Jaw Using Modified Mandibular C-Osteotomies: A Case Report and Review of Literature. (December 2021) - Henry, Andrew M.; Yu, Jason W.; Farrell, Brian B.
The hypoplastic mandible results in facial convergence and pseudo-prognathism. We present a patient with significant maxillary hypoplasia in both the vertical and sagittal dimensions resulting in a reverse occlusal plane. Given the significant maxillary movements required, particularly clockwise rotation, more traditional mandibular osteotomies resulted in an unsatisfactory result. A modified version to the classic "C" osteotomy with the use of surgical planning and cutting guides was performed. A review of the literature on this rarely discussed ramus osteotomy is also presented.